Capital Gains and Spatial Inequalities: Developing Fairer Suburbs. Issue 1 (31st January 2019) - Falk, Nicholas; Manns, Jonathan
Abstract: One of the longest‐running debates in urban development, enshrined within the evolution of the British planning system, is how best to capture the increased value of land arising from development. This article outlines the historic and contemporary context before proposing an approach towards 'land value capture', based on practice in continental Europe but adapted to Britain's specific circumstances. In doing so, it also sets out why new approaches are needed as part of the search for better ways of funding local infrastructure, developing mixed communities and improving Britain's suburbs for the benefit of all.